EVALUASI PERENCANAAN PEMBANGUNAN JALAN MUARA SIBERUT KE DESA MALILIMO (STA. 00+000 S/D 13+000) KECAMATAN SIBERUT SELATAN KEPULAUAN MENTAWAI - Syahrial Effendi; Helga Yermadona; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The construction of a road connecting Muara Siberut Village and Malilimo Village located in the South Siberut District of the Mentawai Islands aims to facilitate transportation flows, connect and open up isolation between 2 regions, namely Muaro Siberut Village and Malilimo Village for the advancement of an area and economic equality. In planning the construction of highways in this writing, it refers to the Geometric planning procedures for Inter-City Roads in 1997 and the Regulations on Geometric Planning for Highways in 1970 issued by the Public Works Service of the Directorate General of Highways. The type of road from Muaro Siberut Village to Malilimo Village is a collector road with class IIA road specifications, pavement width of 2 x 3.5m, planned 22 SCS (Spiral-Circle-Spiral) bends, and 6 FC (Full Circle) bends. (concrete) from Muara Siberut Village to Malilimo Village using rigid concrete pavement types, including: compressive tensile strength of concrete fcf aged 28 days 3.36 Mpa, under foundation CBK (mixed thin concrete) 125 mm, subgrade CBR 3,043 % . 170 mm thick concrete slabKeywords: Geometry Planning Bend S-C-S (Spiral-Circle-Spiral) andf-C (Full Circle), Thickness of Pavement